The Key Attributes of Governance and Capital Structure in Supply Chain Strategy: Complementary or Substitutive Impact? - Ahmed Ibrahim Maymoun Muazeib; Imam Ghozal; Tarmizi Achmad; Faisal Faisal (International Journal of Supply Chain Management, 2019)
This study aimed to investigate the relationship between internal corporate governance attributes and capital structure in a supply chain process of Malaysian listed firms. Most of prior works were based on agency theory, and the results are mixed. This study endeavored to examine the complementary relationship between multiple factors of governance to avoid providing repeated evidences and or to enrich the existing literature with different perspective, which can be achieved by supply chain strategy. The study was conducted in Malaysian listed firm of period 2014-2015. Regression analysis is used in this study as statistical tool of analysis. Based on statistical analysis, the results of this study reveal that only board size, board meeting, and audit committee size are correlated to capital structure. Other variables have no effect on capital structure. The analysis also showed that attributes of governance are complements to each other, in turn; this may lead to perfection of monitoring and management of the board decision making. This study contributes to protect beneficiary parties from manager’s manipulation in a supply chain strategy. Also, the results of this study can be used as a support to develop Malaysian code of governance.